2009
DOI: 10.1080/17538150902773199
|View full text |Cite
|
Sign up to set email alerts
|

Quality of cystic fibrosis information on Italian Websites

Abstract: Given the increased attention on cystic fibrosis care during the last few years in Italy, this study was performed to evaluate content quality, characteristics and completeness of Italian cystic fibrosis websites. GOOGLE was used and retrieved websites were evaluated for the presence of predefined descriptive criteria and disease information. Their contents were compared with available evidence. Thirty sites were evaluated. Few fulfilled the criteria, such as listing authors (24 sites) and citing references (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Several authors investigated quality of information found on the Internet regarding specific health topics, including cystic fibrosis [40], pediatric cancer [41], rheumatologic diseases [42], Mediterranean diet [43]. The search keywords used in these studies were chosen by the authors themselves, either simulating a search by a random user, or simulating a patient’s experience [44].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors investigated quality of information found on the Internet regarding specific health topics, including cystic fibrosis [40], pediatric cancer [41], rheumatologic diseases [42], Mediterranean diet [43]. The search keywords used in these studies were chosen by the authors themselves, either simulating a search by a random user, or simulating a patient’s experience [44].…”
Section: Discussionmentioning
confidence: 99%
“…(1,9,10,20,32,34,35) 23 (5,6,7,8,12,13,14,15,16,17,18,19,21,22,23,24,25,26,29,30,36,37,39) The amount of information available on the Internet is increasing, and thus, concern has been expressed about the quality of this information. Despite this concern, only a handful of studies have recently assessed the quality of health-related information on different topics, such as epilepsy (34), anaesthesia (19,35), breast cancer (23,36), menopause (37), asthma (38), osteoporosis (33), chronic pain (19), scoliosis (39), urology (14,22), anxiety disorders (18) and cystic fibrosis (21). Among these studies, only one was found in the area of dental health describing dental patients' use of the Internet, but this study did not assess the quality of the dental health information (12).…”
Section: Discussionmentioning
confidence: 99%
“…Some articles assess reliability based on the criteria identified by Eysenbach et al (17) in their systematic review of assessing the quality of health information for consumers on the World Wide Web (WWW) (18)(19)(20)(21). Other studies have employed an organization's generic tools or established principles.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this widespread recognition of the importance of health literacy, the quality of educational materials available for patients and families is variable (22,23). Regarding respiratory illnesses, reviews of online patient education materials regarding smoking cessation, asthma, idiopathic pulmonary fibrosis, and cystic fibrosis have found the quality of the materials was often low and sometimes misleading (24)(25)(26)(27)(28)(29). A similar review of chronic obstructive pulmonary disease materials on YouTube showed substantial variation in quality as well (30).…”
mentioning
confidence: 99%